The Arabic writing tradition, an historical survey - Sezgin, Fuat, 1924-2018. (Leiden ; Boston Leiden ; Boston Leiden ; Boston Leiden ; Boston)
<13> cilt (1. c. xiii, 839, [1] sayfa ; 2. c. xv, 670 sayfa ; 3. c. xxi, 418 sayfa ; 4. c. xv, 319 sayfa ; 5. c. viii, 444 sayfa ; 6. c. x, 472 sayfa ; 7. c. viii, 407 sayfa ; 8. c. x, 342 sayfa ; 9. c. x, 360 sayfa ; 10,1 c. xxvi, 526 sayfa ; 11,2 c. vii, 567 sayfa ; 13. c. xiii, 503 sayfa ; 14,1. c. xv, 450 sayfa)
Keywords: “Professor Dr Fuat Sezgin meticulously documented the scientific writings and advances achieved by Muslim scholars. His celebrated Geschichte des arabischen Schrifttums (GAS), the largest bio-bibliography for the Arabic literary tradition in general, and the history of science and technology in the Islamic world in particular, is still of utmost importance for the field“ --